Enhancing Transparency and Accountability: Mosque Financial Information Systems at the Great Mosque of Sidoarjo: Meningkatkan Transparansi dan Akuntabilitas: Sistem Informasi Keuangan Masjid di Masjid Agung Sidoarjo - Rahma , Nabila Novilia; Rahmawati, Imelda Dian (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative research study investigates the role of a financial information system in promoting transparency and accountability within the takmir of the Great Mosque of Sidoarjo. Employing a descriptive research approach, data was gathered through surveys, interviews, and observations. The results demonstrate that the implementation of financial information systems effectively enhances transparency and accountability in managing finances for non-profit entities. Notably, the mosque's website facilitates the creation of financial reports, serving as evidence of financial accountability. Moreover, the open access to financial information Highlight: Efficient Financial Reporting: The mosque's website streamlines financial reporting processes, promoting transparency. Open Access Information: The study underscores the significance of open access to financial information on the mosque's information board. Enhanced Accountability: The research reveals how financial information systems contribute to improved accountability within non-profit entities. Keywords: Mosque, Financial Information System, Transparency, Accountability, Non-profit Entities